The consequences of COVID-19 lockdown for formal and informal resource utilization among home-dwelling people with dementia: results from the prospective PAN.DEM study - Maarja Vislapuu; Renira C. Angeles; Line I. Berge; Egil Kjerstad; Marie H. Gedde; Bettina S. Husebo (BMC, 2021)
Abstract Background COVID-19 isolated home-dwelling people with dementia (PwD) from home care services, respite care, and daytime activities. We aimed to investigate the consequences of these restrictions on informal (family, friends) and formal (homecare staff) resource utilization among co-residing (e.g., spouses) and visiting caregivers (e.g., children). Methods 105 PwD (≥65 years old) and their caregivers were included in the prospective PANdemic in DEMentia (PAN.DEM) study, which was initiated when the ongoing stepped-wedge, cluster randomized LIVE@Home.Path trial (N = 438) was temporarily halted due to the pandemic. Primary outcome was change in resource utilization assessed by the Resource Utilization in Dementia Care (RUD) instrument in pre- (12 Dec. 2019 to 11 Mar. 2020) and during the lockdown periods (20 April 2020 to 15 May 2020). Degree of cognitive impairment was assessed by Mini-Mental Status Examination (MMSE), and physical functioning and independent living skills by Physical Self-Maintenance Scale and Lawton Instrumental Activities of Daily Living Scale. Associations between informal and formal care utilization, socio-demographics, and clinical variables were assessed by descriptive statistics and Ordinary Least Squares models (OLS). Results Mean age for PwD was 81.8 years; 61% were female; 45.6% lived alone, and the mean MMSE score was 20.8 (SD ± 3.7). PwD with co-residents (44%) were younger (78.4 years) than those who were living alone (84.5 years; P < 0.001). During the first 2 months of lockdown, PwD missed on average 20.5 h of formal care in a month (P < 0.001) leading to an approximately 100% increase in informal care, which was particularly pronounced in personal hygiene (6.9 vs. 11.4 days in a month, P < 0.001) and supervision (9.2 vs. 17.6 days in a month; P < 0.001). Visiting caregivers increased by 1.9 days (SD ± 11.5), but co-residing caregivers increased their number of days providing ADL by approximately 7 days per month (β = 6.9; CI, 0.39-13.1, P < 0.05) after adjusting for PwD and caregiver demographics and clinical variables. Decrease in home nursing care was particularly visible for PwD living alone (− 6.1 vs. -1.3 h per month, P = 0.005). Higher cognitive function (β = − 0.64, CI, − 1.26 - 0.02, P = 0.044) was associated with reduction in home nursing service during the lockdown. Conclusion The care situation for PwD changed dramatically in the early phase of the COVID-19 pandemic, especially for those living alone who received less support from homecare services and visiting caregivers. For future crises and the forthcoming post-pandemic period, health authorities must plan better and identify and prioritize those in greatest need. Trial registration ClinicalTrials.gov ; NCT04043364 .